Management of chronic spontaneous urticaria: a worldwide perspective - Pavel Kolkhir; Dmitry Pogorelov; Razvigor Darlenski; Marco Caminati; Luciana Kase Tanno; Duy Le Pham; Alexei Gonzalez-Estrada; Darío Antolín-Amérigo; Ves Dimov; Karsten Weller; Mario Sánchez-Borges; Ignacio Ansotegui; et al. (World Allergy Organization Journal, 2018)
Abstract Background The approaches to the diagnosis and treatment of chronic spontaneous urticaria (CSU) differ in various parts of the world. We sought to determine the adherence to international and national urticaria guidelines as well as the motives to deviate from the guidelines among physicians worldwide. Methods A web-based questionnaire was created and launched via e-mail by the World Allergy Organization (WAO) to representatives of all WAO Member Societies, the members of the American Academy of Allergy, Asthma & Immunology (AAAAI) and the members of the WAO Junior Members Group (JMG), regardless of the specialty, affiliation, or nationality in March 2017. Results We received 1140 completed surveys from participating physicians from 99 countries. Virtually all participants (96%) were aware of at least one urticaria guideline and reported that they follow a guideline. However, one in five physicians who follow a guideline (22%) reported to deviate from it. Reliance on own clinical experience is the most frequent reason for deviation from guidelines or not following them (44%). Young (< 40 years) and less experienced physicians more often follow a guideline and less often deviate than older and experienced ones. Physicians who follow a urticaria guideline showed higher rates of routinely ordering a complete blood count, the erythrocyte sedimentation rate, C-reactive protein, anti-thyroid antibodies, and thyroid-stimulating hormone and of performing the autologous serum skin test as compared to those who do not. Physicians who follow a urticaria guideline showed higher rates of using second generation antihistamines as their first-line treatment of CSU (p = 0.001) and more frequently observed higher efficacy of these drugs (or had more confidence that it would work, p < 0.019) as compared to those who do not follow the guidelines. Conclusions Physicians’ characteristics (e.g. age, clinical experience, and specialty) and country specifics and regional features (e.g. availability of drugs for CSU treatment) importantly influence adherence to urticaria guidelines and CSU patient care and should be addressed in more detail in future research.